Biomechanical Concepts for Fracture Fixation. (December 2015) - Bottlang, Michael; Schemitsch, Christine E.; Nauth, Aaron; Routt, Milton; Egol, Kenneth A.; Cook, Gillian E.; Schemitsch, Emil H.
Abstract : Summary: Application of the correct fixation construct is critical for fracture healing and long-term stability; however, it is a complex issue with numerous significant factors. This review describes a number of common fracture types and evaluates their currently available fracture fixation constructs. In the setting of complex elbow instability, stable fixation or radial head replacement with an appropriately sized implant in conjunction with ligamentous repair is required to restore stability. For unstable sacral fractures with vertical or multiplanar instabilities, "standard" iliosacral screw fixation is not sufficient. Periprosthetic femur fractures, in particular Vancouver B1 fractures, have increased stability when using 90/90 fixation versus a single locking plate. Far cortical locking combines the concept of dynamization with locked plating to achieve superior healing of a distal femur fracture. Finally, there is no ideal construct for syndesmotic fracture stabilization; however, these fractures should be fixed using a device that allows for sufficient motion in the syndesmosis. In general, orthopaedic surgeons should select a fracture fixation construct that restores stability and promotes healing at the fracture site, while reducing the potential for fixation failure. Abstract : Supplemental Digital Content is Available in the Text.